Effect of zinc and iron on growth, oil yield and quality of Japanese mint (Mentha arvensis L.) in sandy loam soil - D Kumar, K Singh, D V Singh, P P Singh, S U Beg (Journal of Spices and Aromatic Crops, 2004)
The results of a field experiment conducted at Lucknow (Uttar Pradesh), to study the effect of different levels of zinc (Zn) (0, 7.5, 15.0 and 22.5 kg ha-1) and iron (Fe) (0, 10.0, 20.0 and 30.0 kg ha-1) on Japanese mint (Mentha arvensis) revealed that fresh herbage, essential oil yield and growth parameters (plant height and leaf area index) increased significantly over control with application of Zn @ 7.5 kg ha-1 and Fe @ 10.0 kg ha-1. Further increase in their doses did not improve the herbage and oil yield. Essential oil concentration in green herbage and its quality of essential oil with respect to major chemical constituents of oil namely, menthol, menthane and menthyl acetate, did not change with application of Zn and Fe.